(?m, f) - Statistical convergence for sequences of fuzzy numbers - Altinok, Hifsi; Deniz, Derya (Ios Press, 2019)
In this paper, we define the concepts of (Delta(m), f)-statistical convergence of order ss and strong (Delta(m), f)-Cesaro summability of order beta for beta is an element of (0, 1] using a generalized difference operator Delta(m) and an unbounded modulus function for sequences of fuzzy numbers and give some inclusion relations between them.
Keywords: Sequence of fuzzy numbers; difference operator; statistical convergence; Cesaro summability; modulus function